Lethal Junctional Epidermolysis Bullosa with Pyloric Atresia due to Compound Heterozygosity for Two Novel Mutations in the Integrin β4 Gene - Stoevesandt, J.; Borozdin, W.; Girschick, G.; Hamm, H.; Höcht, B.; Kohlhase, J.; Volz, A.; Wiewrodt, B.; Wirbelauer, J. (Klinische Pädiatrie, 2012)
Junctional epidermolysis bullosa with pyloric atresia (JEB-PA) is a rare autosomal recessive disease with blister formation within the lamina lucida due to mutations in the integrin β4 (ITGB4) and α6 (ITGA6) genes.A female preterm infant, first child of healthy non-consanguineous parents, was born at 26 + 4 weeks of gestation by caesarean section, following polyhydramnion and abruption of placenta. She presented with extensive areas of denuded skin on both lateral sides of the head, neck and extremities. Auricles were hypoplastic. Abdominal ultrasound and X-ray were suggestive of pyloric atresia which was revised surgically on the 4th day of life. Further course was complicated by progressive skin detachment, sepsis, and renal insufficiency with fatal outcome at 18 days of age. Immunofluorescence mapping of cryopreserved skin showed junctional cleft formation with negative staining for integrin α6 and integrin β4. Mutational analysis disclosed compound heterozygosity for two novel nonsense mutations in the ITGB4 gene: c.600dupC/p.F201fsX14 and c.2533C>T/p.Q845X. 2 subsequent pregnancies were terminated following prenatal diagnosis disclosing the same ITGB4 mutations, a 4th pregnancy was unaffected.We describe a case of lethal JEB-PA with negative immunoreactivity to integrin α6 and integrin β4 predicting a poor outcome. Identification of compound heterozygosity for two novel ITGB4 mutations in the affected preterm infant permitted prenatal diagnosis and finally birth of a healthy sibling.
Keywords: epidermolysis bullosa; pyloric atresia; ITGB4; prenatal diagnosis